Relevansi Kebijakan Literasi Dengan Penguatan Pendidikan Karakter Pada Materi Pokok Madrasah Ibtidaiyah - fifi aris wulandari12; Andi Prastowo (Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2022)
The problem of education is one of the fields which is considered to be very important in the field of government. One of the problems of education is the decline in the quality of reading in students due to lack of literacy that is applied in schools. This article discusses educational policy using literary study methods that use several sources of articles, research and others related to this article that aims to explore the problems and what policies the government is doing to foster literacy at the elementary school level. Ministry of Education and Culture through Minister of Education and Culture Regulation No. 23 of 2015 launched an education policy. This educational policy is in the form of a National Literacy Movement which has 3 domains, one of which is the School Literacy Movement which is used in shaping good moral behavior towards students with language or literacy which is the first step to creating a culture of literacy and the desire to read to students. The School Literacy Movement does not only understand reading and writing skills, but also includes the ability and thoughtfulness of thinking in accordance with the components and stages in literacy. The school literacy movement is expected to be able to bring change both in terms of behavior, attitudes and responsibilities as well as instilling and growing student character values ​​early on, namely the value of independence, nationalism, religious mutual cooperation, and integrity in elementary school students. The character values ​​are also stated in Perpres No. 87 of 2017 concerning Strengthening Character Education (PPK). The National Literacy Movement and the School Literacy Movement are very closely related to the Strengthening of Character Education, because to implement the School Literacy Movement that is in schools and the Strengthening of Character Education can not be said to run optimally but can run when the school institutions and students are active.